Discovery and Preclinical Characterization of 1‑Methyl‑3-(4‑methylpyridin‑3‑yl)‑6‑(pyridin‑2‑ylmethoxy)‑1H‑pyrazolo-[3,4‑b]pyrazine (PF470): A Highly Potent, Selective, and Efficacious Metabotropic Glutamate Receptor 5 (mGluR5) Negative Allosteric Modulator - Zhang, Lei; Balan, Gayatri; Barreiro, Gabriela; Boscoe, Brian P; Chenard, Lois K; Cianfrogna, Julie; Claffey, Michelle M; Chen, Laigao; Coffman, Karen J; Drozda, Susan E; Dunetz, Joshua R; Fonseca, Kari R; et al. (Journal of medicinal chemistry, 2014)
A novel series of pyrazolopyrazines is herein disclosed as mGluR5 negative allosteric modulators (NAMs). Starting from a high-throughput screen (HTS) hit (1), a systematic structure–activity relationship (SAR) study was conducted with a specific focus on balancing pharmacological potency with physicochemical and pharmacokinetic (PK) properties. This effort led to the discovery of 1-methyl-3-(4-methylpyridin-3-yl)-6-(pyridin-2-ylmethoxy)-1H-pyrazolo[3,4-b]pyrazine (PF470, 14) as a highly potent, selective, and orally bioavailable mGluR5 NAM. Compound 14 demonstrated robust efficacy in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-rendered Parkinsonian nonhuman primate model of l-DOPA-induced dyskinesia (PD-LID). However, the progression of 14 to the clinic was terminated because of a potentially mechanism-mediated finding consistent with a delayed-type immune-mediated type IV hypersensitivity in a 90-day NHP regulatory toxicology study.